Thyroid hormone resistance and increased metabolic rate in the RXR-γ–deficient mouse - Brown, Nicole S. (American Society for Clinical Investigation, 2000)
Vitamin A and retinoids affect pituitary-thyroid function through suppression of serum thyroid-stimulating hormone (TSH) levels and TSH-β subunit gene expression. We have previously shown that retinoid X receptor–selective (RXR-selective) ligands can suppress serum TSH levels in vivo and TSH-β promoter activity in vitro. The RXR-γ isotype has limited tissue distribution that includes the thyrotrope cells of the anterior pituitary gland. In this study, we have performed a detailed analysis of the pituitary-thyroid function of mice lacking the gene for the RXR-γ isotype. These mice had significantly higher serum T4 levels and TSH levels than did wild-type (WT) controls. Treatment of RXR-γ–deficient and WT mice with T3 suppressed serum TSH and T4 levels in both groups, but RXR-γ–deficient mice were relatively resistant to exogenous T3. RXR-γ–deficient mice had significantly higher metabolic rates than did WT controls, suggesting that these animals have a pattern of central resistance to thyroid hormone. RXR-γ, which is also expressed in skeletal muscle and the hypothalamus, may have a direct effect on muscle metabolism, regulation of food intake, or thyrotropin-releasing hormone levels in the hypothalamus. In conclusion, the RXR-γ isotype appears to contribute to the regulation of serum TSH and T4 levels and to affect peripheral metabolism through regulation of the hypothalamic-pituitary-thyroid axis or through direct effects on skeletal muscle.